2006
DOI: 10.1017/s0013091502000810
|View full text |Cite
|
Sign up to set email alerts
|

The Polynomial Numerical Index of a Banach Space

Abstract: In this paper, we introduce the polynomial numerical index of order k of a Banach space, generalizing to k-homogeneous polynomials the 'classical' numerical index defined by Lumer in the 1970s for linear operators. We also prove some results. Let k be a positive integer. We then have the following:is sharp.(iii) The inequalities(iv) The relation between the polynomial numerical index of c 0 , l 1 , l∞ sums of Banach spaces and the infimum of the polynomial numerical indices of them.(v) The relation between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 18 publications
0
26
0
3
Order By: Relevance
“…In [7,Proposition 2.8], it is shown that for every k ∈ N the polynomial numerical index of order k of a c 0 -, 1 -, or ∞ -sum of real or complex Banach spaces is less than or equal to the infimum of those indices of the summands. This result is also true for p -sums, and also for absolute sums.…”
Section: Discrete Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In [7,Proposition 2.8], it is shown that for every k ∈ N the polynomial numerical index of order k of a c 0 -, 1 -, or ∞ -sum of real or complex Banach spaces is less than or equal to the infimum of those indices of the summands. This result is also true for p -sums, and also for absolute sums.…”
Section: Discrete Resultsmentioning
confidence: 99%
“…The proof for the cases p = 1, ∞ appears in [7,Proposition 2.8]. That proof is easy to extend to an arbitrary absolute sum.…”
Section: Discrete Resultsmentioning
confidence: 99%
See 3 more Smart Citations